Gaussian graphical model for Perceiving the Sense of Community of Melanau Coastal Village in Mukah, Sarawak - Mohamad Hardyman, Barawi; Noor Fazilla, Abd Yusof; Donald, Stephen; Mohd Kamal, Othman; Zaimmuariffudin Shukri, Nordin; Mukhriz Izraf Azman, Aziz (Machine Intelligence Research Labs., 2024)
This paper reports the findings of the Sense of Community (SoC) investigation using a partial correlation network analysis model within the Melanau community in Mukah, Sarawak. This study intended to investigate the neighbourhood structure and interactions among Melanau households. A sample of 85 households from three (3) Melanau coastal villages have participated in the survey and completed the questionnaires. The collected data has been analysed using regularised partial correlation network analysis (EBICglasso). The findings from this study proved that the support from leaders and community members are strongly related. However, the connection between these two nodes and other nodes in the network is relatively weak. This study also suggests that caring for other community members is the most central node; the participation in the community events is the most peripheral node in the sense of community network among the Melanau community. The insights from this study shed light on the associations of neighbourhood environment and sense of community. Thus, facilitating an informed decision-making process which could help researchers and policymakers understand the climate of SoC for intervention planning in the Melanau community.